2012
DOI: 10.1590/s0104-11692012000100018
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization of children under five years of age due to avoidable causes

Abstract: This study characterizes the profile of hospital morbidity according to the main diagnosis upon admission, in individuals younger than five years old, residents of three cities 16.1% in hospital admissions of patients younger than five years old in relation to the total number of admissions in all age groups. As for the main diagnoses, there were diseases of the respiratory system (55.6%), infectious and parasitic diseases (14.8%) and diseases originating in the perinatal period (12.9%). Such conditions can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
11

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 14 publications
0
10
0
11
Order By: Relevance
“…Estudos realizados em outras cidades brasileiras também evidenciaram estas como as principais responsáveis por internações infantis (6,17,20) . Cabe destacar que enquanto os outros estudos apontaram as afecções perinatais como a terceira causa de hospitalização, esses agravos foram responsáveis por menos de cinco internações hospitalares por mil crianças no período estudado, sendo classificado no presente estudo, como outras doenças.…”
Section: Discussionunclassified
“…Estudos realizados em outras cidades brasileiras também evidenciaram estas como as principais responsáveis por internações infantis (6,17,20) . Cabe destacar que enquanto os outros estudos apontaram as afecções perinatais como a terceira causa de hospitalização, esses agravos foram responsáveis por menos de cinco internações hospitalares por mil crianças no período estudado, sendo classificado no presente estudo, como outras doenças.…”
Section: Discussionunclassified
“…A study which aimed to assess the reliability of SIH-SUS data by comparing data with information on the patient forms suggested that 20% of ACSC admissions were not recorded (3) . However, a number of studies have highlighted the importance of investigations based on data from the SIH-SUS and consider the system an important source of data for assessing PHC (2,6,10) .…”
Section: Discussionmentioning
confidence: 99%
“…Admissions among children under the age of one are generally due to problems in the quality of prenatal care, which is part of primary health care, but are also related to birth and new born care which fall under hospital care (10) . Nevertheless, perinatal conditions, which account for a large part of admissions among children under the age of one, may be considered potentially avoidable (2) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations